DevOps Metrics. - FORSGREN, NICOLE; KERSTEN, MIK (Communications of the ACM, 2018)
The article discusses the measuring of DevOps implemented in organizational contexts. Topics include the need to create a baseline for the measurement of DevOps, the use of system-based metrics, and characteristics of system data. The use of survey-based metrics is addressed in relation to software development and delivery.